Image of Childhood in Some of Blake's Poems - Hadi S. Sultan (PROSPECTIVE RESEARCHES, 2023)
One of the Romantic poets who devotes a notable area for childhood in his poetry is William Blake. He does not look at childhood as a golden period of his life like other Romantic poets. Instead, he tests this period through other children whom he sees and observes. In this sense, he looks at this subject objectively. As a result, he depicts children in different moods and conditions. He also attributes the different moods of children to different situations, persons, and institutions. He, sometimes, identifies himself with the children's life, now as a victim now as a saviour. Hence, Blake is sincere in this field. He glorifies the children's happiness and gives indirect solutions for their sufferings.